Introducing blueberry powder as one of the first complementary foods changes the gut microbiota composition and diversity in U.S. human milk-fed infants: a double-blind, randomized controlled trial - Glime, Gabrielle N. E.; Matzeller, Kinzie L.; Frank, Daniel N.; Kotter, Cassandra; Kofonow, Jennifer M.; Robertson, Charles E.; Venter, Carina; Campbell, Wayne W.; Krebs, Nancy F.; Tang, Minghua (Frontiers in Nutrition, 2025)
IntroductionComplementary feeding is a critical period marked by rapid changes in the infant’s diet, nutrient needs, and gut microbiota. However, the effects of specific foods introduced during complementary feeding, such as blueberries, on the developing infant gut microbiota remain unclear. Our primary aim was to evaluate the effect of daily consumption of freeze-dried blueberry powder during complementary feeding on gut microbiota development in U. S. human-milk-fed infants.MethodsIn a double-blind, randomized, placebo-controlled feeding trial, infants from the Denver metro area (Colorado, United States) were randomly assigned to consume up to 10 g of freeze-dried blueberry powder or an isocaloric placebo powder, combined with liquid or semi-liquid and served as a puree, daily from 5 to 12 months of age. Stool samples were collected bimonthly to assess gut microbial diversity and composition. Novel taxa were identified through parsimony insertion into the SILVA reference phylogenetic tree. Infant length, weight and dietary intakes were also assessed.ResultsSeventy-six caregiver-infant pairs consented and enrolled in the study and 61 completed the study (blueberry group n = 30, placebo group n = 31). There were no differences between groups in energy or macronutrient intakes from complementary foods. Growth z-scores were comparable between groups. Gut microbiota alpha diversity increased over time in both groups (effect of time p < 0.001). Several taxa, including Veillonaceae, Flavonifractor, Subdoligranulum, and Butryicicoccus (all more abundant in the blueberry group), and Actinomyces, Escherichia, Streptococcus, and Romboutsia (more abundant in the placebo group) had group-by-time interactions that trended toward significance.ConclusionIntroducing blueberries as one of the first complementary foods, in the form of freeze-dried powder served as a puree, exerts potential benefits in gut microbiota development and maturation in this cohort of human-milk-fed infants.Systematic review registrationhttps://clinicaltrials.gov/study/NCT05006989.